Kepentingan Strategis ITB Sebagai Aktor Nonteritorial Transnasional Bidang Iptek - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2006)
The globalization ambivalence era requires a nation to be more anticipative than just reactive to a change taking place in the world so that the nation is able to sustain its existence in the world. Another character that complements this anticipative character i.e. non-territorial transnational actor (ANT) is also needed by a nation to prolong the nation's existence. Institut Teknologi Bandung (ITB), as one of Indonesia's ANTs, can play its role in introducing both Indonesia's traditional or indigenous and intellectual knowledge to the international community. This role may soon be realized if ITB's community is willing to change its by sector policy into a policy with which ITB (as an ANT) can make the best use of one of its main assets: grey Literature in its interaction with the international community. Grey Literature is defined as an entity representing the whole ITB's intellectual experience. To accomplish this role, a set of ITB's strategic programs is descibed. One of the programs is to make the best use of all Indonesia's embassies to be ITB's grey Literature agent and relate it with the 8 (eight) leading edge technologies that are predicted to be dominant worldwide in the future.